Additive Manufacturing Capabilities for Emergency Manufacturing in Healthcare How Additive Manufacturing Capabilities Can Be Utilised to Increase Healthcare Resilience in the Event of a Crisis - Hörnell, Martin; Lindahl, Ludvig (My University, 2024)
Disruptions in global supply chains can severely impact the availability of medical equip- ment. Additive manufacturing (AM) presents a potential solution for the on-demand, decentralised production of critical medical parts. This master’s thesis investigates the current capabilities of AM for medical equipment manufacturing and what role AM could have in improving the supply chain resilience of medical equipment during a cri- sis. A comprehensive literature review of AM capabilities for medical equipment and areas surrounding the implementation of AM in healthcare, along with data collection through 17 semi-structured interviews with personnel from hospital 3D units and AM companies were conducted. The results of this study suggest that AM capabilities can be used to produce certain critical medical equipment to improve healthcare resilience. Furthermore, AM was found to enable a decentralised manufacturing structure that can further be used to improve resilience toward supply disruptions. This presents an opportunity to create a national collaboration to develop, manufacture and deliver critical items at shorter lead times and increase supply chain robustness. On this ba- sis, this study presents a recommendation to map the existing AM capabilities and production sites and establish collaborations between 3D units and AM companies to manage decentralised manufacturing at various scales effectively. Given the novelty of AM in medical equipment and the limited research that has been conducted in this field, further research is needed to better understand AM’s capabilities and factors for a successful implementation.
Keywords: Additive manufacturing; Medical equipment; Decentralised production; Supply disruptions